Philosophy of Culture on the Philosophy of Modern Education in China - Cai Yonghong; M. N. Fomina (Концепт: философия, религия, культура, 2023)
In Chinese philosophy, modern processes of searching for the fundamental values of the renewed strategies of education are based upon traditional Confucian approaches as well as upon recent borrowings from Western philosophy. The concept of philosophical dialogue is one example of these borrowings, adopted and radically changed following traditional Chinese logic. Such transformation means adapting the theoretical model of Socrates’ dialogue into Confucian dialogue, the term coined by Chinese authors. This paper considers Chinese developments in the philosophy of culture and aims to specify the ways of such adaptation as applicable to the philosophy of education. The goals of the study are 1) to identify and describe relevant Chinese literature on the subject; 2) to compare its interpretations by Chinese and Russian philosophers; 3) to specify key differences in interpretations of dialogue as educational method. Investigating the issue through philosophical and cultural lens, incorporating the standpoint of modern comparative studies, as well as the critical analysis of the logic of those theories in their historical and cultural context by means of the hermeneutic approach makes it possible for Chinese authors to focus on the cultural peculiarities of the Chinese way of thinking and to identify the correlation between the Western concept way of thinking and the concept of Chinese logic. This study analyzes the works of modern Chinese philosophers specializing in the specific cultural character of China through the prism of the philosophy of education. The paper concludes that in Chinese logic technical (in the Western understanding regarded as cognitive and formal logical) methods are inferior to ethical and social value orientations. Another finding is that Chinese authors tend to consider Confucian logic as part of dialogue, and dialogue is viewed as a means of moral education. Methodologically this finding leads the author to suggest that the Chinese-specific way of thinking, its philosophical culture, cannot be fully perceived by utilizing comparison with analogous concepts of Western philosophical thought. It would be equally beneficial to compare the conceptual framework of the Chinese philosophy of education with the concepts borrowed from Western philosophy.